Chronic exposure to polyethylene and tire wear particles changes the associative behaviour in cyprinid fishes - Sakshi R. Tripathi; Pankaj A. Gorule; Marek Šmejkal; Vlastimil Stejskal; Filip Ložek; Alessandro Cau (Environmental Pollution, 2026)

A train of marine heat waves affected benthic local beta but not alpha diversity - Laura Carugati; Davide Moccia; Alessandro Cau; Vincenzo Donnarumma; Antonio Pusceddu (Marine Environmental Research, 2026)

Fiber entanglements as a proxy for anthropogenic pollution uptake: Monitoring deep-water rose shrimp (Parapenaeus longirostris) throughout the year - María Ariadna Redón-Morte; Ester Carreras-Colom; Lorenzo Chiacchio; Alessandro Cau; Oriol Rodríguez-Romeu; Anna Soler-Membrives (Environmental Pollution, 2026)

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Weathered microplastics alter deep sea benthic biogeochemistry and organic matter cycling: insights from a microcosm experiment - Claudia Dessì; Stefano Aliani; Vincenzo Donnarumma; Maria Cristina Follesa; Davide Moccia; Giuseppe Suaria; Andrea Paluselli; Alessandro Cau (Environmental Pollution, 2025)

Microplastics impair extracellular enzymatic activities and organic matter cycling in oligotrophic sandy marine sediments - Alessandro Cau; Davide Moccia; Claudia Dessì; Laura Carugati; Ester Carreras-Colom; Fabrizio Atzori; Nicoletta Cadoni; Antonio Pusceddu (Science of The Total Environment, 2024)

Shedding Light on the Italian Mesophotic Spongofauna - Margherita Toma; Marzia Bo; Marco Bertolino; Martina Canessa; Michela Angiolillo; Alessandro Cau; Franco Andaloro; Simonepietro Canese; Silvestro Greco; Giorgio Bavestrello (Journal of Marine Science and Engineering, 2024)
An analysis of 483 remotely operated vehicle (ROV) dives carried out along the Italian coast on hard substrata at mesophotic depths (40–200 m) allowed an overview of the rich sponge diversity (53 taxa) of the deep continental platform to be obtained for the first time. About 40% of the potential actual species diversity was recognisable using ROV, suggesting that this group is among the richest yet underestimated using this technology in contrast to other megabenthic taxa. Additionally, the study allowed us to gather data on the current basin-scale distribution and bathymetric limits of five common and easily identifiable demosponges with up to 55% occurrence in the explored sites: Aplysina cavernicola, the group Axinella damicornis/verrucosa, Chondrosia reniformis, Foraminospongia spp., and Hexadella racovitzai. Four of these latitudinal distributions were characterised by high occurrence in the Ligurian Sea and a progressive decrease towards the south Tyrrhenian Sea, with an occasional second minor peak of occurrence in the Sicily Channel. In contrast, Foraminospongia spp. showed a maximum occurrence on the offshore reliefs and a second one in the North–central Tyrrhenian Sea, while it was almost absent in the Ligurian Sea. Trophic and biogeographic reasons were discussed as possible causes of the double-peak distributions. The vertical distributions support a more consistent occurrence of all considered taxa in deeper waters than previously known. This suggests that they may more typically belong to the mesophotic realm than the shallow waters, owing to a more extensive sampling effort in the deeper depth range. The five target taxa are typical or associated species of seven reference habitats in the recently revised UNEP/SPA-RAC classification. However, they may create such dense aggregations that they should be listed as new facies in the abovementioned classification.

Marine macro-litter mass outweighs biomass in trawl catches along abyssal seafloors of Sardinia channel (Italy) - Ester Carreras-Colom; Maria Cristina Follesa; Laura Carugati; Antonello Mulas; Andrea Bellodi; Alessandro Cau (Environmental Science and Pollution Research, 2024)
This study provides new insights onto spatial and temporal trends of seafloor macro-litter in the abyssal seafloor of Sardinian channel, in central western Mediterranean (Italy). Trawl surveys were conducted at depths between 884 and 1528 m, thus focusing on one of the least investigated marine environments. None of the considered sites was litter free, with plastics being numerically dominant (57% of items), followed by metal (11%) and glass (16%). Recorded densities and weight ranged between 49.9 and 499 items km −2 and 1.4 and 1052 kg km −2 . In the most contaminated sites, the weight of the litter collected in nets represented up to nine times the biomass of benthic megafauna, and, overall, in 60% of hauls macro-litter mass outweighed the biomass collected. Moreover, we report that megafauna was observed to be more abundant in sites where macro-litter presence was more severe. More studies are needed to elucidate the nature of this correlation, with biota being more abundant in hotspots of accumulation of seafloor macro-litter.

What, where, and when: Spatial-temporal distribution of macro-litter on the seafloor of the western and central Mediterranean sea - Alessandro Cau; Alice Sbrana; Simone Franceschini; Fabio Fiorentino; Maria Cristina Follesa; Francois Galgani; Germana Garofalo; Olivia Gerigny; Adriana Profeta; Paola Rinelli; Mario Sbrana; Tommaso Russo (Environmental Pollution, 2024)

Long-term sublethal exposure to polyethylene and tire wear particles: Effects on risk-taking behaviour in invasive and native fish - Pankaj A. Gorule; Marek Šmejkal; Sandip Tapkir; Yevdokiia Stepanyshyna; Vlastimil Stejskal; Maria Cristina Follesa; Alessandro Cau (Science of The Total Environment, 2024)

Jaws from the deep: biological and ecological insights on the kitefin shark Dalatias licha from the Mediterranean Sea - Massimiliano Bottaro; Mauro Sinopoli; Iacopo Bertocci; Maria Cristina Follesa; Alessandro Cau; Ivan Consalvo; Faustino Scarcelli; Emilio Sperone; Marino Vacchi; Letizia Marsili; Guia Consales; Roberto Danovaro (Frontiers in Marine Science, 2023)
Due to their late maturation, extreme longevity, low fecundity and slow growth rates, deep-sea Chondrichthyes are extremely vulnerable to human impacts. Moreover, assessing the impact of deep-sea fisheries is difficult, as many species (including sharks) are part of the bycatch and are often discarded at sea, and/or landed under generic commercial-species codes. The lack of this information on fishery data sets and the limited availability of species-specific life history data make challenging the management of deep-sea Chondrichthyes. The kitefin shark Dalatias licha is a cosmopolitan elasmobranch, mainly found on continental and insular shelf-breaks and slopes in warm-temperate and tropical waters. This species is a common by-catch of the deep-sea trawling, considered as “Endangered” by the IUCN Red List for all European waters, Mediterranean Sea included. Here we present the results of a study based on a total of 78 specimens of kitefin shark collected over 3 years in the Ligurian Sea (NW Mediterranean) as by-catch from deep-water fisheries. Total length ranged from 380 to 1164 mm, and individual weight ranged from 198 to 8000 g. Immature and mature individuals showed a sex ratio dominated by males. Adult males were observed throughout the year, while mature females were observed only in spring-summer. These data lead to hypothesise a spatial segregation between genders. The kitefin shark diet was dominated by bony fish (mainly Macrouridae) and other small sharks (e.g., Galeus melastomus and Etmopterus spinax ), but their gut included plastic items and parasites. Data reported here underline the rarity, complex ecology and the threat for this shark species and support the urgency of promoting initiatives for their monitoring and conservation.

Comparative microplastic load in two decapod crustaceans Palinurus elephas (Fabricius, 1787) and Nephrops norvegicus (Linnaeus, 1758) - Alessandro Cau; Pankaj A. Gorule; Andrea Bellodi; Ester Carreras-Colom; Davide Moccia; Lucia Pittura; Francesco Regoli; Maria Cristina Follesa (Marine Pollution Bulletin, 2023)

Commercial sharks under scrutiny: Baseline genetic distinctiveness supports structured populations of small-spotted catsharks in the Mediterranean Sea - Riccardo Melis; Laura Vacca; Alessia Cariani; Laura Carugati; Alessandro Cau; Charis Charilaou; Simone Di Crescenzo; Alice Ferrari; Maria Cristina Follesa; Farid Hemida; Sarah Helyar; Sabrina Lo Brutto; et al. (Frontiers in Marine Science, 2023)
The present study, based on microsatellite markers, describes a population genetic analysis of the small-spotted catshark Scyliorhinus canicula (Linnaeus, 1758), representing one of the most abundant and commonly caught cartilaginous fishes in the Mediterranean Sea and adjacent areas. The analyses were performed to unravel the genetic features (variability, connectivity, sex-biased dispersal) of their relative geographic populations, both at the small (around the coast of Sardinia, Western Mediterranean Sea) and at a larger spatial scale (pan-Mediterranean level and between the Atlantic Ocean and the Mediterranean Sea). Individual clustering, multivariate and variance analyses rejected the hypothesis of genetic homogeneity, with significant genetic differences mainly within the Mediterranean between the Western and Eastern basins, as well as between the Mediterranean and the NE Atlantic Ocean. In detail, our results seem to confirm that the Strait of Gibraltar could not represent a complete barrier to the exchange of individuals of small-spotted catshark between the Atlantic Ocean and the Mediterranean Sea. In the latter area, a complex genetic structuring for S. canicula was found. Apart from differences among the Western, Eastern and Adriatic sites, within the Western basin the small-spotted catsharks around Sardinian waters are strongly differentiated from all others (both from the eastern Tyrrhenian Sea and southernmost part of the Algerian basin) and are demographically stable. Several possible mechanisms, both biological and abiotic (e.g., migratory behavior, waterfronts, and oceanographic discontinuities), are discussed here to explain their peculiar characteristics. Overall, the genetic data presented, both at the local and regional level, could represent a baseline information, useful for the temporal monitoring of populations, and to assess the effects of present or future fishing/management/conservation measures.

Late Quaternary sedimentary record of estuarine incised-valley filling and interfluve flooding: The Manfredonia paleovalley system (southern Italy) - Alessandro Amorosi; Luigi Bruno; Massimo Caldara; Bruno Campo; Simone Cau; Vincenzo De Santis; Andrea Di Martino; Wan Hong; Giorgio Lucci; Claudio Pellegrini; Veronica Rossi; Irene Sammartino; et al. (Marine and Petroleum Geology, 2023)

A Year of Bio-Monitoring (2021): Presence of Algae of the Genus Alexandrium, Dinophysis, Prorocentrum and Non-Compliance for Paralytic Toxins and Lipophilic Toxins in Bivalve Mollusks Bred in Sardinia (W Mediterranean Sea) - Giuseppa Lorenzoni; Anna Maria Bazzoni; Monica Cangini; Sonia Dall’Ara; Rita Melillo; Alessandro Graziano Mudadu; Simona Cau; Barbara Soro; Salvatore Ledda; Gabriella Piras; Tiziana Tedde; Sara Salza; et al. (Journal of Marine Science and Engineering, 2022)
Bivalve mollusk production represents the principal aquaculture activity in Sardinia (40°03′ N, 9°05′ E). In 2021, 859 water samples and 1270 mollusk samples were analyzed. The species Alexandrium minutum caused the accumulation of Paralytic Shellfish Toxins (PST) in three samples of bivalve mollusks. Dinophysis acuminata complex caused the accumulation of lipophilic toxins (LTs) belonging to the okadaic acid group (OAs) in 18 samples of bivalve mollusks. The research of paralytic shellfish toxins (PSTs) in shellfish samples has been carried out with LC-FLD, as mentioned in the AOAC 2005 Official Method 2005.06. The determination of LTs was carried out by LC-MS/MS analysis. DTX2, belonging to the group of OA toxins, was detected for the first time in Sardinia, in mussels sampled in Tortolì. The presence of Dinophysis and Prorocentrum species was correlated with the accumulation of the OA toxin group in bivalve mollusks, showing a certain repeatability at certain times of the year in the areas included in the study. The results of the present study can help to plan and organize more effective bio-monitoring sampling strategies.

Structure and status of the Italian red coral forests: What can a large-scale study tell? - Margherita Toma; Marzia Bo; Daniele Giudice; Simonepietro Canese; Alessandro Cau; Franco Andaloro; Michela Angiolillo; Silvestro Greco; Giorgio Bavestrello (Frontiers in Marine Science, 2022)
The precious coral Corallium rubrum (Linnaeus, 1758) is a charismatic Mediterranean species. A recent large-scale investigation along the Italian coast highlighted its widespread occurrence at mesophotic and upper bathyal depths, especially on coralligenous and bathyal vertical hardgrounds. The lack of morphometric data limited the considerations on the structure and health status of the populations, fundamental to identify the most vulnerable sites and the correct management actions. For this reason, a ROV dataset, consisting of 624 dives carried out between 40 m and 1825 m in the Ligurian Sea, Tyrrhenian Sea, and Sicily Channel, was analysed to extrapolate quantitative data to describe the populations. Ten random frames were obtained from each of the 170 sites hosting red coral. Density, height, and entanglement were evaluated for about 15700 colonies counted in the frames. The densest populations were mainly found between 40 m and 80 m, with a clear latitudinal density decrease. The mesophotic populations were characterized by both scattered and densely aggregated colonies, while the bathyal ones were dominated by sparse colonies. This study identified 17 major coral areas based on the geographic proximity of the sites hosting red coral and their topographic and oceanographic affinity. The size-frequency distribution of the heights was skewed towards the smaller classes in almost all populations, with a modal class between 2 cm and 4 cm. This study depicted a stress situation of the populations throughout the entire study area, which could be correlated also to the long-term harvesting pressure carried out in the basins. Two additional sources of direct mortality were pointed out in this study. Entanglement to artisanal and recreational fishing gear interested about 18% of the recorded colonies, mainly at mesophotic depths. Almost all populations suffered from mechanical entanglement, with the highest percentages in the Ligurian Sea and Sicilian areas. This study also highlighted a massive occurrence of recent deep mortality events, mainly along the eastern and southern coast of Sardinia and in the Campanian Archipelago. Thirty sites with extensive patches of dead colonies still in place were reported from 70 m to around 200 m, but their formation remains unclear.

Spatio-temporal distribution of Isidella elongata, a vulnerable marine ecosystem indicator species, in the southern Adriatic Sea - Pierluigi Carbonara; Walter Zupa; Maria Cristina Follesa; Alessandro Cau; Marilena Donnaloia; Sébastien Alfonso; Loredana Casciaro; Maria Teresa Spedicato; Porzia Maiorano (Hydrobiologia, 2022)

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

Basin-scale occurrence and distribution of mesophotic and upper bathyal red coral forests along the Italian coasts - MARGHERITA TOMA; MARZIA BO; RICCARDO CATTANEO-VIETTI; SIMONEPIETRO CANESE; MARTINA CANESSA; RITA CANNAS; FRINE CARDONE; LAURA CARUGATI; ALESSANDRO CAU; GIUSEPPE CORRIERO; MARIA CRISTINA FOLLESA; MARIA MERCURIO; et al. (Mediterranean Marine Science, 2022)
The analysis of 879 ROV dives carried out along the Italian coasts on hard substrata at mesophotic and upper bathyal depths (40-775 m) allowed us to evaluate the current basin-scale presence, relative abundance, bathymetric limits, and habitat preferences of one of the most charismatic Mediterranean habitat-former anthozoan species, Corallium rubrum (Linnaeus, 1758). The species is widespread, and its occurrence ranged from 13% of the explored sites in Ionian Calabria to a hotspot of approximately 80% in Sardinia. Population relative densities were generally low (

Eating Near the Dump: Identification of Nearby Plastic Hotspot as a Proxy for Potential Microplastic Contamination in the Norwegian Lobster (Nephrops norvegicus) - Simone Franceschini; Alessandro Cau; Lorenzo D’Andrea; Maria Cristina Follesa; Tommaso Russo (Frontiers in Marine Science, 2021)
Plastic waste dumped in the marine environment has severe ecological, social and economic impacts. In recent years, a series of scientific studies documented the contamination by macroplastic and its impact on marine organisms through the accidental ingestion of microplastics, which also originate from the degradation of macroplastic. However, the relationship between the spatial distribution of marine litter and the ingestion of plastics by organisms have never been related. In this work, we aimed to investigate, through a modeling approach, the relations between potential sources of microplastic particles (i.e., seafloor macroplastic accumulation hotspots detected by means of trawl surveys), and the ingestion by the benthic crustacean Norwegian lobster ( Nephrops norvegicus ). According to the literature, N. norvegicus is characterized by a sedentary behavior and therefore it has been highlighted as a proficient sentinel species for local microplastic contamination. Despite no significant relation has been found between microplastic ingestion and the local presence of seafloor macroplastic, it seems that proximity to hotspots of macroplastic accumulation is significantly related to microplastics ingestion. These results highlight important considerations on the fate of plastic in the marine environments with significant impacts on biota and the quality of the product caught at sea.

Molecular and Biological Analysis on Ommastrephes caroli Findings in the Central Western Mediterranean Sea (Sardinian Waters) Including First Age Investigation Using Eye Lenses and Beaks - Blondine Agus; Laura Carugati; Andrea Bellodi; Rita Cannas; Alessandro Cau; Jacopo Cera; Elisabetta Coluccia; Riccardo Melis; Stefano Ruiu; Danila Cuccu (Frontiers in Marine Science, 2021)
Molecular identifications based on two mitochondrial markers (cytochrome c oxidase subunit I -COI- and 16S ribosomal RNA gene -16S-) have been implemented to confirm the morphological identification of eight specimens collected in the Central western Mediterranean. Molecular data show they belonged to a recently resurrected species of the genus Ommastrephes , i.e., O. caroli , known to be distributed in the Atlantic Ocean and Mediterranean Sea. Despite this, molecular analyses of COI sequences evidenced the presence of potential genetic differentiation between Mediterranean and Atlantic samples, highlighting the need for further studies, with more individuals to investigate the connectivity between individuals living in the two areas. Furthermore, morphological, biometric and reproductive features here reported, could be useful in evaluating possible distinctive biological features between the Mediterranean and Atlantic individuals. Female mature size was larger than the male. The relationships obtained between the beak measurements and body sizes (DML; TW) were better described by a power model. Asynchronous oocytes development with relatively small oocytes (0.05–1.10 mm) and a protracted intermittent spawning with active feeding were observed. This study also reported for the specie O. caroli the first data on the potential fecundity estimated (840061 oocytes), the oviducal load (90000 ripe oocytes) as well as the number of seminal receptacles and the size and morphology of the spermatangia found in the buccal mass of all mated females. Even if on a low sample size, beaks and eye lenses were used for the first time in O. caroli for age estimation. The statistically significant relationship found between increments counted in eye lenses and beaks highlighted the reliability of the lenses to estimate age in O. caroli , even if further studies will be needed for its validation. Assuming a daily increment for both structures, a mean life span of about 12–13 months was estimated for both sexes, which is consistent with the sexual maturity condition observed in all the samples and the semelparity known for cephalopods coleoids.

Longitudinal Study on Seasonal Variation of Marine Biotoxins and Related Harmful Algae in Bivalve Mollusks Bred in Sardinia (Italy, W Mediterranean Sea) from 2015 to 2020 and Assessment of Potential Public Health Risks - Alessandro G. Mudadu; Anna Maria Bazzoni; Virgilio Congiu; Giuseppe Esposito; Alberto Cesarani; Rita Melillo; Giuseppa Lorenzoni; Simona Cau; Barbara Soro; Bruna Vodret; Domenico Meloni; Sebastiano Virgilio (Journal of Marine Science and Engineering, 2021)
Annual and interannual dynamics of shellfish toxins and associated harmful algal species (HAS) were analyzed from 2015 to 2020 in Tortolì Lagoon (Sardinia, west Mediterranean Sea). Analysis of seasonal occurrence of different harmful algae, such as Dinophysis spp., Prorocentrum spp., Pseudo-nitzschia spp. and Alexandrium minutum, was performed. The species Dinophysis acuminata and Dinophysis sacculus were responsible for the accumulation of lipophilic toxins belonging to the okadaic acid group (OAs) and pectenotoxins2 (PTX2) in bivalve mollusks. The highest HAS detection was recorded in the winter months; in particular, Dinophysis spp. was mostly present in January–February. Out of 1090 analyzed mollusk samples, 39 were non-compliant, exceeding the legal limits (160 μg OA eq/kg e.p.) reported in Regulation 853/2004 of the European Commission. A statistical analysis related to the presence of OA and PTX2 in mollusks with various environmental parameters (pH, water temperature, dissolved oxygen, algal density) was implemented, proving a clear winter seasonality. The present study highlights the necessity to better understand the different factors able to influence the production and accumulation of toxins in bivalve mollusks bred in an important Sardinian production area. The contribution of this research is important not only from an environmental and productive point of view but also from the view of implementing management in order to mitigate any harm to human health.

On the presence of the Endangered white skate Rostroraja alba in Sardinian waters - MARTINA FRANCESCA MARONGIU; CRISTINA PORCU; ANDREA BELLODI; RITA CANNAS; LAURA CARUGATI; ALESSANDRO CAU; ANTONELLO MULAS; PAOLA PESCI; MARIA CRISTINA FOLLESA (Mediterranean Marine Science, 2020)
The white skate Rostroraja alba is assessed by the International Union for Conservation of Nature as Endangered globally and is now considered rare in the Mediterranean. This species has never been recorded in Sardinian seas (central western Mediterranean), but an empty eggcase was collected on a sandy bottom off the western Sardinia coasts during the MEDiterranean International Trawl Survey (MEDITS) program in 2019. A morphometric and morphological description of the Sardinian eggcase, after a comparison with measurements from other Mediterranean and Atlantic specimens, showed it to be clearly ascribable to Rostroraja alba.

Living naked: first case of lack of skin‐related structures in an elasmobranch, the blackmouth catshark ( Galeus melastomus ) - Antonello Mulas; Andrea Bellodi; Cristina Porcu; Alessandro Cau; Elisabetta Coluccia; Riccardo Demurtas; Martina Francesca Marongiu; Paola Pesci; Maria Cristina Follesa (Journal of Fish Biology, 2020)
As far as is known, in this paper the first case of lacking of skin‐related structures (epidermis, stratum laxum , dermal denticles and teeth) in a free‐swimming elasmobranch, the blackmouth catshark, Galeus melastomus , is reported. The individual was caught by trawl in Sardinian waters (central‐western Mediterranean) in July 2019 at a depth of 500 m. Although this kind of morphological abnormality is potentially fatal, the observations suggested that the specimen was in good health and well developed.

Onboard Scientific Observers Provide a Realistic Picture of Harvesting and Management Priorities for the Precious Red Coral (Corallium rubrum L.) - Laura Carugati; Alessandro Cau; Maria Cristina Follesa; Riccardo Melis; Davide Moccia; Cristina Porcu; Susanna Salvadori; Rita Cannas (Frontiers in Marine Science, 2020)

Resource partitioning among sympatric elasmobranchs in the central-western Mediterranean continental shelf - Antonello Mulas; Andrea Bellodi; Rita Cannas; Pierluigi Carbonara; Alessandro Cau; Martina Francesca Marongiu; Paola Pesci; Cristina Porcu; Maria Cristina Follesa (Marine Biology, 2019)

Fragment quality and sediment organic loading regulate the survival of an invasive, clonal seaweed - Fabio Bulleri; Laura Tamburello; Antonio Pusceddu; Lisa Bonechi; Alessandro Cau; Davide Moccia; Paul E. Gribben (Biological Invasions, 2018)

Investigation on the genus Squalus in the Sardinian waters (Central-Western Mediterranean) with implications on its management - ANDREA BELLODI; CRISTINA PORCU; ALESSANDRO CAU; MARTINA FRANCESCA MARONGIU; RICCARDO MELIS; ANTONELLO MULAS; PAOLA PESCI; MARIA CRISTINA FOLLESA; RITA CANNAS (Mediterranean Marine Science, 2018)
In the Mediterranean Sea, in addition to the two historically known species belonging to the Squalus genus, a third species, Squalus megalops, has been reported. Considering the high level of morphologic similarity of this species with the native species S. blainville, this study aims to evaluate the Central-Western Mediterranean spurdog population in order to test the hypothesis of the presence of two distinct species S. blainville and S. megalops. A total of 137 spurdogs, caught in the Sardinian waters, were analyzed morphologically and genetically after their subdivision into two groups depending on the number of the lateral processes in the chondrocranium basal plate. The CAP analysis, employing all body and chondrocranial measurements, revealed no clear segregation among the a priori assigned groups with a high misclassification percentage. Besides, no evident dissimilarities in teeth and dermal denticle morphology between the two groups were observed. All the 18 specimens which were genetically analyzed, by sequencing of the mtDNA marker COI, clustered together resulting to be S. blainville. All the obtained results indicated the presence, in the study area, of only one species, ascribable to S. blainville.

Age determination of Loligo vulgaris and Loligo forbesii using eye lens analysis - Blondine Agus; Marco Mereu; Rita Cannas; Alessandro Cau; Elisabetta Coluccia; Maria Cristina Follesa; Danila Cuccu (Zoomorphology, 2018)

Genetic population structure and phylogeny of the common octopus Octopus vulgaris Cuvier, 1797 in the western Mediterranean Sea through nuclear and mitochondrial markers - Riccardo Melis; Laura Vacca; Danila Cuccu; Marco Mereu; Alessandro Cau; Maria Cristina Follesa; Rita Cannas (Hydrobiologia, 2018)

New insights into connectivity patterns of mesophotic red coral (Corallium rubrum) populations - Rita Cannas; Flavio Sacco; Alessandro Cau; Elisabetta Coluccia; Maria Cristina Follesa; Angelo Cau (Hydrobiologia, 2015)

Deepwater corals biodiversity along roche du large ecosystems with different habitat complexity along the south Sardinia continental margin (CW Mediterranean Sea) - Alessandro Cau; M. Cristina Follesa; Davide Moccia; Andrea Alvito; Marzia Bo; Michela Angiolillo; Simonepietro Canese; Enrico M. Paliaga; Paolo E. Orrù; Flavio Sacco; Rita Cannas (Marine Biology, 2015)

Temporal dynamics of demersal chondrichthyan species in the central western Mediterranean - Marongiu Martina; Porcu Cristina; Bellodi Andrea; Cau Alessandro; Mulas Antonello; Follesa Maria (Frontiers in Marine Science, 2015)